Direct electrodeposition of imidazole modified poly(pyrrole) copolymers: synthesis, characterization and supercapacitive properties. (20th July 2017) - Wolfart, Franciele; Hryniewicz, Bruna M.; Marchesi, Luís F.; Orth, Elisa S.; Dubal, Deepak P.; Gómez-Romero, Pedro; Vidotti, Marcio
Graphical abstract: Abstract: In this manuscript we report the direct electrosynthesis of a new conducting copolymer based on the incorporation of imidazole molecules within the polypyrrole chain. Different proportions of the monomers were tested during the direct electropolymerization of the copolymer. The resulting materials were characterized by electrochemical and spectroscopic techniques (Raman and XPS) and a mechanism of polymerization is proposed. Our findings showed that imidazole acts as an inhibitor of the polymerization process, decreasing the overall number of actives sites for the polymerization on the electrode surface producing a polymeric morphology very different compared with pure polypyrrole, as observed by Scanning Electron Microscopy images and corroborated by Electrochemical Impedance Spectroscopy. This behavior significantly affects the supercapacitive performance of the resulting p(Py-IMZ) modified electrodes where the specific capacitance of the material increased from 122 to 201 Fg −1 (64%) at 10 mV s −1 . Furthermore, a unique pseudo-capacitive behavior described herein emphasizes the role of the imidazole as inductor of the morphology and co-monomer in the unique electrochemical signature of the material. The results suggest that the incorporation of IMZ increases the specific capacitance of PPy electrode by around 64%.